Sustainability of cassava (Manihot esculenta Crantz) as industrial feedstock, energy and food crop in Nigeria. (September 2015) - Anyanwu, C.N.; Ibeto, C.N.; Ezeoha, S.L.; Ogbuagu, N.J.
Abstract: Nigeria's cassava production surpassed 30 MMT around 1994 and has been increasing at 4.3% per annum. Cassava production targets under the government's agricultural transformation agenda program appear achievable, but it is unclear if current cassava output can satisfy growing demands. Yields need to increase from 12 t/ha currently to 25 t/ha by 2015 as specified in the ATAP. Cassava peels can yield 0.6 l/kg TS of biogas, which could augment primary energy needs. About 1.0 × 10 9 L of bioethanol could be produced annually from over 7.0 MMT of cassava peels generated, which is sufficient to execute government's E10 program. Graphical abstract: Highlights: Twenty-year data for cassava production and yield in Nigeria are presented. Production and yield figures are compared with the ATAP targets. Food uses of cassava are highlighted. Alternative applications of cassava for biofuels and other industrial demands are presented. Potential uses of cassava waste for energy needs in Nigeria are assessed.